(untitled) (Colombia Medica, 1989)
This study included the morbidity and mortality analysis on selected samples from 2,300 patients who attended the Outpatients Department, 1,444 patients at the Emergency Service, and 6386 discharges. In the outpatient departments, females were 63.6%, and patients aged 15 years or over were 93.9% females were 57.5% of the Emergency Service. The 65.5% were people aged 15-44 years. Females comprised 65% of the discharges department, and 61% corresponded to those aged 15-44. The Basic Tabulation List (BTL) shows a predominance of female consultations caused by the illness of the connective and muscular systems and endocrine immune and metabolic diseases. In contrast, a significant number of male consultations were done because of other reasons. The leading specific cause of morbidity was hypertensive cardiac disease. It was followed by diabetes mellitus, pharyngitis, conjunctivitis, and rheumatoid arthritis. At the Emergency Service, according to sex, the morbidity first two groups were signs, symptoms, and miss definite morbid states and diseases from other parts of the digestive system. Trauma was the main problem of hospitalization, with an average of 17.8% of discharges. The first two groups were other accidents, including delayed effects, and internal intracranial traumas, including nerve trauma. Surgical treatment represented 80%, and the permanence average in the first seven groups was 9.6 days. The rate of hospital mortality was 8.6% Remission from other institutions was 12.4% at the Outpatients Department and 12.2% at the Emergency Service.